A Case of Overlap Posterior Cortical Atrophy and Logopenic Variant Primary Progressive Aphasia. Issue 2 (March 2019) - Fitzpatrick, Donal; Blanco-Campal, Alberto; Kyne, Lorraine
Abstract : Posterior cortical atrophy (PCA) and logopenic variant primary progressive aphasia (LvPPA) are considered early-onset dementias most commonly caused by Alzheimer pathology. PCA is characterized by a progressive decline in higher order visual processing functions, whereas LvPPA is a form of primary progressive aphasia. The clinical presentation of both syndromes is typically earlier in life relative to the more typical "amnestic" form of Alzheimer disease. Prominent language deficits have been well described in PCA. Here, we describe the case of a 56-year-old man presenting with overlapping anatomic, clinical, and cognitive features of PCA and LvPPA and review the existing literature relating to the clinical features shared by these conditions, exploring the etiology, and implications for clinical practice in cases with a PCA-LvPPA overlap syndrome. In PCA, atrophy occurs in temporoparietal-occipital regions, whereas in LvPPA atrophy occurs at the temporoparietal junctions, with left-sided predominance. A defective phonological loop (a short-term storage system which holds speech sounds in memory for 1 to 2 s) seems to underlie the logopenic syndrome in both conditions. Other parietal lobe deficits, in proximity to both language and visual processing areas, such as dyscalculia and ideomotor apraxia are also commonly found in both conditions. We suspect that cases with an overlap PCA-LvPPA syndrome are relatively underreported which may relate to the fact that these cases occur on a spectrum depending on the stage of disease progression and do not easily fit into strict diagnostic categories according to existing criteria of PCA and LvPPA, respectively.